Perfil epidemiológico de los pacientes ingresados a la Unidad de Dolor Músculo-esquelético del Servicio de Medicina Física y Rehabilitación del Hospital Clínico Universidad de Chile - Ruiz R., Delia; Miranda M., Ana Luisa; Castro L., Ariel (Revista Hospital Clínico Universidad de Chile, 2015)
Pain is an individual and subjective experience, recognized as an important public health issue. Further, pain is a complex phenomenon which needs a transdisciplinary approach. Objective: To describe the epidemiological characteristics of patients admitted in a Pain Unit. Methods: We performed an observational prospective study that analyzed the medical records of patients who attend the Pain Clinic, at the Rehabilitation Unit in the University of Chile Clinical Hospital, between April 2012 and April 2013. Results: Women are more frequently affected by pain (78.50%), with a mean age of 54 years old. The mean duration of pain was 1.76 years and the most common presentation was low-backache (54.21%) with moderate intensity. Most of the patients were taking painkillers (75.70%), preferably paracetamol and NSAIDs. 47.66% suffered from mixed pain and a 92.52% manifested chronic pain. Myofascial pain and osteoarthritis were the more frequent causes. After admission, a more appropriated treatment was prescribed in all of the patients, most of them consisting in opioids and antiepileptic drugs, associated with interventional techniques (60.75%). As a consequence, 67.09% of the patients had a significant decrease in pain intensity. Conclusion: It is necessary to generate epidemiological research lines that support health policies and allows a transdisciplinary pain management.